Способ повышения магнитной индукции в зазоре электромеханических преобразователей энергии с постоянными магнитами - Афонин, А.А. (Видавничий дім "Академперіодика" НАН України, 2007)
An approach to the design of combined magnetic systems with complex configurations of permanent magnets and concentrators of a magnetic flow is proposed. It is shown that such systems allow one to increase the magnetic flow densities in the air gaps of electromechanical energy converters with inner rotor.